Kegiatan Alpha Zone dalam Mengembangkan Kecerdasan Interpersonal Siswa di MIM PK Kartasura Tahun Ajaran 2016/2017 - Saputri, Lulut Dian, Muhroji, M.Si, M.Pd., SE (2017)
This study aimed to describe the activities of Alpha Zone in developing interpersonal intelligence IIB and VIA grade students at MIM PK Kartasura. This research is a type of qualitative research. Design of this research is phenomenology. The technique used to collect data by performing interviews, observation, and documentation. Checking the validity of the data in this research is using triangulation. The results showed that the activities of Alpha Zone is one of the actions the teacher to develop students' interpersonal intelligence. By administering the Alpha Zone there is an element of cooperation will be established communication between students so that students who lack interpersonal intelligence will be trained to communicate and familiar with his friends. The survey results revealed that some of the problems that occur in interpersonal intelligence that is difficult for students to communicate well with the teacher and the student. In addition, students who experience problems with interpersonal intelligence tend to be passive in the activities of Alpha Zone as well as the difficulties in cooperating in groups and tend to be shunned by other students.